Cloning of a novel Bacillus pumilus cellobiose-utilising system : functional expression in Escherichia coli - Van Rooyen, Ronel, 1976- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2002.